Management of project risks in decommissioning (Safety reports series, 2019)
"This safety report publication provides specific guidance on the management of project risks in decommissioning. The publication proposes a systematic and pro-active approach on how to identify, analyse, evaluate, and treat relevant project risks at strategic and operational levels, and provides examples of application of the proposed approach."--Publisher's description